Building and ornamental use of trachyte in the center of France during antiquity: Sources and criteria of identification. (September 2015) - Boivin, Pierre; Miallier, Didier; Cluzel, Nicolas; Devidal, Jean-Luc; Dousteyssier, Bertrand
Abstract: The volcanic field of Chaîne des Puys (French Massif Central) includes six trachytic volcanoes, the lavas of which were more or less extensively exploited during antiquity and medieval ages as a raw material for construction, sculpture and fabrication of sarcophagi. Recent questioning on the origin of trachytes from the famous Mercury sanctuary (2nd centuries AD) built atop Puy de Dôme volcano motivated the launch of a program devoted to establish source identification criteria for trachytic artifacts based on petrography, geochemistry and mineralogy These analyses allowed to establish a list of very strong criteria allowing to distinguish each volcano. The nature of the minerals being discriminating in most cases, a small sample size is sufficient for the diagnosis. The possibilities offered by the new classification are illustrated by a reappraisal of trachyte supplying around Augustonemetum (Clermont-Ferrand) during the Gallo-Roman period. In the course of this program, we discovered a previously unknown major quarry of trachyte. Highlights: Trachyte was privileged for building and sculpture during antiquity in the centre of France. The potential sources of trachyte are 6 volcanoes only, situated in the Chaîne des Puys. The 6 trachytes can be differentiated by their petrographic and geochemical features. A database for identifying trachytic artifacts was established. A previously unknown quarry appeared to be the most important one for the Gallo-Romans.